Price, Service Quality and Trust on Tokopedia Towards Customer Satisfaction - Jeremy Iron Wiratama; Muhammad Agung Hidayatullah; Innocentius Bernarto; Lamhot Henry Pasaribu (Institute of Computer Science (IOCS), 2021)
This study aims to analyse 1) Does price have a positive effect on Tokopedia customer satisfaction?, 2) Does service quality have a positive effect on Tokopedia customer satisfaction?, 3) Does trust have a positive effect on Tokopedia customer satisfaction? In searching the data, questionnaires were used and distributed to Tokopedia e-commerce users, where respondents were domiciled in Greater Jakarta, especially in Jakarta and Tangerang. The sampling method of this research is purposive sampling, which the number of samples is 164 people. In this study, the data analysis method used was PLS-SEM. This study shows that service quality and trust have a positive effect on customer satisfaction, while price does not have a positive effect on customer satisfaction. The results of this study can be a contribution to the Tokopedia company to maximize customer satisfaction from Tokopedia and also to develop strategies to increase Tokopedia customer satisfaction.